Simple Thermal Analysis as a Green Method for the Detection of Meat Adulteration - Ilma Nugrahani; Aditya Aditya (Indonesian Journal of Chemistry, 2023)
Differential scanning calorimetry (DSC) is one of the most widely developed thermal analysis methods for meat samples for halal authentication of food or processed products. Research on adulteration detection for various types of meat and its derivatives has been developed before and still requires organic solvents. Therefore, the concept of the "green method" is being tried to develop in this research. DSC analyses are performed in the same experimental conditions for all sample powder: sample mass 2 mg, temperature range 30–400 °C, and heating rate 20 °C min−1. The results showed there is a characteristic minor endothermic peak for each meat. Chemometric analysis was carried out using the principal component analysis (PCA) method to ensure that the thermal characteristics of each meat were utterly different in both pure and mixed meat. The results of this analysis indicate that each pure meat has a different score plot. Therefore, the developed thermal analysis method is quite reliable in determining the different types of meat based on the characteristic minor endothermic peak in the thermogram and the score plot from PCA analysis.